Value co-creation between public service organizations and the private sector: An organizational capabilities perspective - Jonathan Rösler; Tobias Söll; Louise Hancock; Thomas Friedli (Administrative Sciences, 2021)
Theoretically based on public service logic (PSL), this paper explores the barriers and capabilities surrounding public sector value co-creation with private sector organizations in the context of digital transformation. Specifically, value co-creation efforts at a large public transport and rail infrastructure provider are examined from multiple perspectives using an exploratory case study approach. Based on qualitative interview data, six barriers that hinder value co-creation in public service ecosystems and five corresponding organizational capabilities required to overcome them are identified. The study contributes to the field of public management research by shedding light on the concept of value co-creation in public-private sector digitalization collaborations.
Keywords: 350; barriers; digital transformation; organizational capabilities; public sector innovation; service innovation; value co-creation